A alternativa que corresponde à solução de
∫ 2x ln(x) dx
é:
Anexos:
![](https://pt-static.z-dn.net/files/db8/5c7b0205ab92e8b21ad3b87a7312c39b.png)
Soluções para a tarefa
Respondido por
0
Resposta:
∫ 2x * ln(x) dx
Fazendo por partes
u=ln(x) ==> du =(1/x) dx
dv=2x dx ==> ∫ dv=∫ 2x dx ==> v =x²
∫ 2x * ln(x) dx =x²*ln(x) - ∫ x² * (1/x) dx
∫ 2x * ln(x) dx =x²*ln(x) - ∫ x dx
∫ 2x * ln(x) dx =x²*ln(x) - x²/2 + c
Perguntas interessantes
Matemática,
9 meses atrás
Matemática,
9 meses atrás
Espanhol,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás